Evaluating the Impact of Formative Assessment Intervention and Experiences of the Standard 4 Teachers in Teaching Higher-Order-Thinking Skills in Mathematics - Moyo, Sello Editor; Combrinck, Celeste; Van Staden, Surette (Frontiers in Education, 2022)
Formative assessment may be a useful pedagogical practice to enhance the teaching of HOTS in mathematics. This study explored the impact of a formative assessment intervention on 1) students’ achievements in HOTS mathematics tests (pre-and-post) when their teachers were supported to implement the instructional intervention and 2) Standard 4 (Grade 4) teachers’ formative assessment practices. To explore the effects of 2-day intervention for professional development teacher training, this study employed mixed methods, sequential embedded approach with single-group, pre-test, intervention (training), and post-test instruments. Data were gathered from nine primary schools involving nine teachers and 272 standard 4 students in the southern region of Botswana. Students’ tests scales were used to measure achievement in mathematical HOTS items along with classroom observations and interviewed the teachers’ experiences and reflections. Students’ achievement data were assessed for internal reliability and validity by applying the Rasch Partial Credit Model followed by descriptive analysis and Wilcoxon signed-rank testing. The observed and interviewed teacher data were analyzed by descriptive frequency counts and thematic analysis, respectively. The students’ achievement in mathematically HOTS items was found significantly improved from pre-test to post-testing. Post-intervention classroom observation showed that teachers practised the integration and implementation of some formative assessment strategies. Finally, the teachers’ experience and reflections were found to be favorably inclined to support formative assessment higher-order thinking skills as a strategy to enhance mathematics teaching.